Baikalobia elochinensis sp. n. (Plathelminthes, Tricladida, Continenticola), a new species of endemic Baikal planarians: morphological and genetic comparison with the type species Baikalobia guttata (Gerstfeldt, 1858) - Porfiriev, Andrey; Koroleva, Аnastasia; Kiril’chik, Sergey; Timoshkin, Оleg (Zootaxa, 2018)
Endemic freshwater planarians of the family Dendrocoelidae (Plathelminthes, Tricladida, Continenticola) are characteristic components of the Baikal fauna. Despite the long history of research on this group, new species and genera of Baikal planarians have been regularly described (Porfirieva, 1977; Timoshkin et al., 2004; Porfiriev et al., 2009; Porfiriev et al., 2011; Porfiriev and Timoshkin, 2013; Porfiriev and Timoshkin, 2015).